Iloprost Drug Delivery during Infant Conventional and High‐Frequency Oscillatory Ventilation. (1st March 2016) - DiBlasi, Robert M.; Crotwell, Dave N.; Shen, Shuijie; Zheng, Jiang; Fink, James B.; Yung, Delphine
Abstract : Iloprost is a selective pulmonary vasodilator approved for inhalation by the Food and Drug Administration. Iloprost has been increasingly used in the management of critically ill neonates with hypoxic lung disease. This in vitro study was designed to test the hypothesis that aerosol drug delivery could be effectively administered to infants with both conventional ventilation and high‐frequency oscillatory ventilation (HFOV). A neonatal test lung model configured with newborn lung mechanics was ventilated with a conventional ventilator and an HFOV with standard settings. A vibrating‐mesh nebulizer was placed (1) proximal to the patient airway in the inspiratory limb between the humidifier probe and patient wye (conventional) as well as between the vent circuit and the endotracheal tube (ETT) for HFOV and (2) between the ventilator and humidifier (distal). Iloprost was nebulized in three separate runs using three new nebulizers in each of the circuit locations. A collecting filter was placed at the distal end of the ETT for each trial. Iloprost was quantified using high‐performance liquid chromatography. The percentage of nominal dose delivered was greater with the nebulizer placed proximal to the airway for conventional ventilation (10.74% ± 2%) and HFOV (29% ± 2%) than with it placed in the distal position (2.96% ± 0.2% vs. 0.96% ± 0.8%, respectively; P < 0.05). Drug delivery in proximal position was nearly threefold greater during HFOV than during conventional ventilation. In conclusion, iloprost drug delivery was best achieved when the nebulizer was placed proximal to the patient airway during neonatal mechanical ventilation. Drug delivery appears to be more efficient during HFOV than during conventional ventilation.